Perioperative lung protection - Marseu, Katherine (Korean J Anesthesiol, 2017)
Perioperative pulmonary complications are known to be a major cause of morbidity and mortality, and as such, contribute a large burden to the health care system globally. Anesthesiologists have an important role during the perioperative period to identify patients at risk of these complications and intervene in order to reduce them. After describing perioperative pulmonary complications and risk factors for such, this article will address preoperative, intraoperative, and postoperative lung protective strategies to try and reduce the risk of these complications.